'The Need for Translation': The Role of Translation in Eavan Boland's Work. (March 2021) - Trachsler, Virginie
Abstract : This article provides an overview of the place translation holds in Eavan Boland's career, taking in her experience as a reader of translations as well as a translator, showing how the first fed into the second and how her own practice evolved using examples from her whole career. It then focuses on her bilingual anthology of German poets After Every War to demonstrate that her work as a translator stemmed from the same ethical and poetic concerns as her work as a poet, retrieving marginal voices and creating an alternative tradition around female experiences. The Classical myth of Ceres and Persephone, which Boland revisited and rewrote many times, shows how her translation practice lastingly influenced her poetics and poetry.